DEBUNKING THE RELATIONSHIP BETWEEN LAW AND CAPITALISM: HOW CORPORATE GOVERNANCE FAILURES CONTRIBUTE TO THE FINANCIAL CRISIS IN INDONESIA? - Sopian, Najmu Laila; Salampessy, Muhammad Yahdi (UI Scholars Hub, 2016)
The recent global financial catastrophe has raised questions about the relationship between corporate governance and the crisis. Many scholars attribute the crisis to the corporate failure and the Anglo-Saxon model of capitalism. Much of the literatures, however, tend to focus on examining the issue of financial crisis in the developed economy. Following up this line of literatures, this paper will extend the discussion of the role of corporate governance in financial crisis in the developing world. Using Indonesia as a case study, this paper will look at evidence that has emerged from the recent financial crisis regarding the failures of corporate governance in addressing and preventing the crisis.